Engaged to London's wildest billionaire - Anthony, Kali (Anthony, Kali. Behind the palace doors, 2023)
In the words of the devil himself: "Scandal I can do..." Lance Astill's debauched reputation is the stuff of tabloid legend. He's dedicated to rebelling against his strict aristocratic upbringing and has never once shied away from trouble. Until he meets Sara Conrad... Entertaining thoughts of his attraction to sheltered Sara would be far too reckless. Even for him. Then Sara makes him an impassioned plea to help her escape an arranged wedding, just like the one Lance failed to save his sister from. The playboy's outlandish solution? Their own headline-making engagement!